PERTANGGUNGJAWABAN PIDANA BAGI PELAKU TINDAK PIDANA PENCURIAN DALAM KEADAAN MEMBERATKAN (ANALISIS PUTUSAN PENGADILAN NEGERI SUKADANA NOMOR: 36/Pid.B/2024/PN Sdn.) - Arya Dwi Bangga, Cendys; Anita Sinaga, Niru (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Crime is a deviant act, which has a reprehensible nature, so that this act often causes social reactions in society, while human efforts to completely eradicate this crime are often carried out, but the results are more likely to fail, so other efforts that can be made are by means of suppress or reduce the rate of crime. Several acts or acts that violate the law and disturb the peace and harmony of living together, one of which is the crime of theft accompanied by violence, which we can see almost every day in electronic media and in the mass media. As happened in the city of Lampung, which is still within the territory of the Sukadana District Court, which has the authority to examine and adjudicate, someone has taken something, which wholly or partly belongs to another person, with the intention of possessing it unlawfully, which was done by two or more people in partnership., which to enter the place of committing a crime, or to get to the goods taken, is done by breaking, cutting, or climbing, or by using a fake key, a fake order, or fake official clothes. The formulation of the research problem is how is the crime of theft regulated in aggravating circumstances based on Indonesian criminal law? And what is the criminal responsibility for perpetrators of criminal acts of theft in aggravating circumstances in the Sukadana District Court decision number: 36/pid.b/2024/PN.Sdn.? The research method used in this research is normative juridical legal research. The approach method used in this research is the statutory approach. Apart from that, the author also uses the conceptual approach method and the case approach method. The research results show that the regulation of criminal acts of theft in aggravating circumstances according to criminal law in Indonesia has been regulated and the decision of the Panel of Judges at the Sukadana District Court Number 36/Pid.B/2024/PN Sdn is in accordance and does not conflict with applicable regulations.